Solar Energy Is an Important Trend in The Development of The Energy Sector in Poland - Agnieszka MAZUREK-CZARNECKA (Communications of International Proceedings, 2021)
The aim of the article is an attempt to join the multi-threaded discussion regarding the necessity of increasing use of renewable energy sources in the process of obtaining energy. The article presents a thesis that the increase in the use of renewable energy sources in the energy production process may contribute to the independence and energy sovereignty of the state and reduce electricity costs. The article focuses on the relationship between the energy sector and the economy, and refers to the need to develop the energy sector in Poland, so far based on hard coal and lignite. Reference was also made to the need to combat climate change in the context of the current pandemic. The current data on the use of electricity consumption in Poland, the increase in energy imports from abroad and the level of energy production from individual sources are presented. A significant increase in the installed photovoltaic capacity was also referred to. The article uses the desk research method, which consists in analyzing aggregated data from secondary sources.
Keywords: Energy; Solar Energy; Renewable Energy Sources